New insights of phenolic compounds from optimized fruit extract of Ficus auriculata - Shahinuzzaman M.; Akhtar P.; Amin N.; Ahmed Y.; Anuar F.H.; Misran H.; Akhtaruzzaman M. (Nature Research, 2023)
antioxidant; phenol derivative; plant extract; solvent; centrifugation; chemistry; Ficus; filtration; fruit; isolation and purification; ultrasound; Antioxidants; Centrifugation; Ficus; Filtration; Fruit; Phenols; Plant Extracts; Solvents; Ultrasonic Waves